Empathy-based Counseling Guidance and Teacher Social Support for Children's Self-Confidence - Manik, Resmin (Journal of Childhood Development, 2026)
This study aims to examine the effect of empathy-based counseling and teacher social support on the self-confidence of early childhood children in Palangka Raya City. This study used a quantitative approach with a causal associative method. The study subjects consisted of 150 children aged 5-6 years and 50 early childhood education teachers selected using the proportional method. Cluster Random Sampling. Data collection used a questionnaire for the teacher variable and structured observation for the child's self-confidence variable, which was then analyzed using SmartPLS . The results of the study showed that empathy-based counseling had a positive and significant effect on children's self-confidence (t count 4.512>1.980; p =0.000). Teacher social support has a significant effect on children's self-confidence (t count 3.890>1.980; p =0.002). Simultaneously, both variables contribute a strong influence of 65.4% t count 12.450; R2 = 0.654). This statistical finding is supported by triangulation of observational data, which shows a change in children's behavior from withdrawn to engaged after receiving emotional validation and instrumental support. This study concludes that the integration of counseling guidance carried out by teachers as therapeutic helpers through empathy and social support is an important determinant in shaping children's self-confidence.